Plasmaconcentration-time data for amoxicillin in cats - Ekstrand, Carl; Roques, Beatrice (Swedish University of Agricultural Sciences, 2025)
The data set consist of amoxicillin plasma concentrations after treatment of six cats with three different pharmaceutical preparations and routes of administration in a non-randomized cross-over study. Moreover, data on binding to plasma proteins are included.

Data består av plasmakoncentrationer av amoxicillin över tid efter behandling av sex katter med tre olika beredningsformer och administrationsvägar i en orandomiserad cross-over studie. Utöver rådata finns uppgifter om proteinbindningsgrad.
Plasmakoncentration-tidsdata för amoxicillin hos katt
Keywords: Amoxicillin; Amoxicillin; Felis; Felis; pharmacokinetics; farmakokinetik; pharmacology; farmakologi; felis catus linnaeus, 1758; plasma concentration; plasmakoncentration; Pathobiology; Patobiologi; Other Veterinary Science; Annan veterinärmedicin